Odpowiedzi

Najlepsza Odpowiedź!
2009-11-14T13:51:53+01:00
(2x² -4x -10) :⅔= (2x² -4x -10)*3/2=6/2x²-12/2x-30/2=3x26x-15

12xy-20x
__________________= 3xy-5x
4

-2√2(a+√2b)-4(a√2-2b)=-2√2a-4b-4a√2+8b=-6√2a+4b
2009-11-14T13:53:00+01:00
1)
(2x² -4x -10) :⅔= 2(x²-2x - 5) x 3/2 = 3x²-6x -15

2)
12xy-20x/4 = 4(3xy - 5x)/4 = x(3y - 5)

3)
-2√2(a+√2b)-4(a√2-2b)= - 2a√2 - 4b - 4a√2 + 8b = -6a√2 + 4b =
= 2(2b - 3a√2)
2009-11-14T13:59:38+01:00
A)
(2x²-4x-10): ⅔ = (2x²-4x-10) × ³/₂ = 3x² - 6x - 15

b)
12xy-20x / 4= 4(3xy-5x) / 4 = 3xy-5x

c)
-2√2(a+√2b)-4(a√2-2b)= -2a√2 -4b -4a√2 +8b = -6a√2 +4b